Microbial community succession of cow manure and tobacco straw composting - Liu, Songqing; Zhao, Juan; Feng, Wen-Long; Zhang, Zong-Jin; Gu, Yun-Fu; Wang, Yan-Ping (Frontiers in Microbiomes, 2024)
Composting livestock manure using microorganisms is a harmless and resourceful practice. The continual fluctuations in physicochemical parameters during composting are intricately linked to the composition of microbial communities. This study delved into the dynamics of microbial communities during the composting of cow manure and tobacco straw using amplicon sequencing and shotgun metagenomics. The sequencing results unveiled major genera such as Sphaerobacter, Actinomadura, Thermomonospora, Flavobacterium, Bacillus, Hydrogenophaga, Pseudomonas, Lysinibacillus, Aneurinibacillus and Azotobacter. Metagenomics analysis highlighted that the phylum Proteobacteria constituted the largest proportion. Furthermore, the presence of genus Rhodococcus, known to cause human and animal diseases, gradually decreased over time. These findings offer initial insights into the microbial community composition and function during cow manure and tobacco straw composting.